Identification of Resistant Genotypes on Rice against Blast Disease under Field Condition at Rampur, Chitwan - Rijal, Tirtha Raj; Hamal, Govinda Bahadur; Jha, Purushhotam; Koirala, Keshab Babu (International Journal of Applied Sciences and Biotechnology, 2017)
Blast disease is considered as a major limiting factor in the global rice production because of its wide distribution and destructiveness and it has been causing significant yield loss in all rice growing areas of Nepal. Host resistance is the most desirable means of managing blast, especially in developing countries. Considering the importance of this disease field screening experiment was conducted to identify resistant rice genotypes against this disease. A total of 314 and 346 rice genotypes with resistant (Sabitri) and susceptible checks (Sankarika) were evaluated under epyphytotic conditions during 2016 and 2017 summer seasons at Rampur, respectively. During 2016 disease severity varied from 1 to 9 and only five genotypes; Sabitri, IR 12L 110, WAS122-IDSA14-WASB-FKRI, IR 10F 559and IR 10F 616 were resistant, 30 moderately resistant, 150 susceptible and 129 highly susceptible against blast disease. Similarly during 2016 out of 346 genotypes, 23 resistant as ARIZE SWIFT GOLD, IR95784-21-1-1-2, NR2169-10-4-1-1-1-1-1-2, NR2169-10-2-3-1-1-1-1-1, NR2181-165-1-1-1-1-1-1-1, NR2167-48-5-1-2-1-1, NR2171-2-1-1-3-1-1-2, NR2170-5-5-1-6-1-1-3-1, NR2170-31-1-1-5-1-1-1-1, NR2167-41-1-1-3-1, NR2172-34-1-1-1-1-1-1-1, Sabitri, IR82589-B-B-114-3, IR79913-B-238-3-3, IR93823-36, IR08L 152, IR82589-B-B-51-4, IR09F 434, IR55423-01, IR94391-131-353-19-B-1-1-1-1-1, NR2154-8-1-1-1-1-1, NR 2124-43-3-1-1-1, NR2160-68-1-1-1-1-1., 72 moderately resistant, 191 susceptible and 155 were highly susceptible. Most of the highly susceptible genotypes were knocked down at the time of disease scoring. Int. J. Appl. Sci. Biotechnol. Vol 5(4): 505-510